LOOKING FOR A ROAD TO GET OUT OF POVERTY. IS THE CURRENT ALLOCATION OF PUBLIC SPENDING ON EDUCATION IN COLOMBIA HELPING? (Artículo publicado en inglés) (Estudios Gerenciales, 2004)
This paper presents a methodology to explore the impact on poverty of the public spending on education. The methodology consists of two approaches: Benefit Incidence Analysis (BIA) and behavioral approach. BIA considers the cost and use of the educational service, and the distribution of the benefits among groups of income. Regarding the behavioral approach, we use a Probit model of schooling attendance, in order to determinethe influence of public spending on the probability for thepoor to attend the school. As a complement, a measurement of targeting errors in the allocation of public spending is included in the methodology.